PERJUANGAN MASYARAKAT KERINCI MENENTANG KOLONIALISME BELANDA 1901-1942 - Mizwan, Aldi; Yanto, Ferry; Azmi, Ulul (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This purpose of this study is analyze how Kerinci society organized and resisted the Dutch Colonialism, as well as the impact of the againt on social, economic and political development in the Kerinci region. The research method used is a historical method consisting of several steps, namely heuristics, criticism, interpretation, historiography. The primary sources used in this study are interviews and archives, skunder sources used in the form of books, theses and other references. The results of this study will help to better understand the againt of the Kerinci people against Dutch colonialism, as well as its impact on the development of the Kerinci region after the colonial period. It will also provide a broader view of local resistance to colonialism in areas not much explored in Indonesian history.